Hospitalisations for heart failure predict mortality in pulmonary hypertension related to congenital heart disease. Issue 6 (29th September 2018) - Ntiloudi, Despoina; Apostolopoulou, Sotiria; Vasiliadis, Konstantinos; Frogoudaki, Alexandra; Tzifa, Aphrodite; Ntellos, Christos; Brili, Styliani; Manginas, Athanasios; Pitsis, Antonios; Kolios, Marios; Karvounis, Haralambos; Tsioufis, Costas; et al.
Abstract : Objective: Despite the progress in the management of patients with adult congenital heart disease (ACHD), a significant proportion of patients still develop pulmonary hypertension (PH). We aimed to highlight the rate of the complications in PH-ACHD and the predicting factors of cumulative mortality risk in this population. Methods: Data were obtained from the cohort of the national registry of ACHD in Greece from February 2012 until January 2018. Results: Overall, 65 patients receiving PH-specific therapy were included (mean age 46.1±14.4 years, 64.6% females). Heavily symptomatic (New York Heart Association (NYHA) class III/IV) were 53.8% of patients. The majority received monotherapy, while combination therapy was administered in 41.5% of patients. Cardiac arrhythmia was reported in 30.8%, endocarditis in 1.5%, stroke in 4.6%, pulmonary arterial thrombosis in 6.2%, haemoptysis in 3.1% and hospitalisation due to heart failure (HF) in 23.1%. Over a median follow-up of 3 years (range 1–6), 12 (18.5%) patients died. On univariate Cox regression analysis history of HF hospitalisation emerged as a strong predictor of mortality (HR 8.91, 95% CI 2.64 to 30.02, p<0.001), which remained significant after adjustment for age and for NYHA functional class. Conclusions: Long-term complications are common among patients with PH-ACHD. Hospitalisations for HF predict mortality and should be considered in the risk stratification of this population.